Reference birthweight range for multiple birth neonates in Japan - Kato, Noriko (BioMed Central, 2004)
BACKGROUND: A reference range for the birthweight of multiple births neonates is necessary for the assessment for intrauterine growth. METHODS: Pairs of multiple births were identified by birthplace, the ages of the parents, gestational age, and the year and month of birth. We studied a total of 32,232 livebirth-livebirth pairs of twins, 1894 triplet live births, and 206 quadruplet live births. RESULTS: The median birthweight of males, taking gestational age into account, was ca. 0.05 kg–0.1 kg heavier than that of females. Compared to singleton neonates, the median birthweight of twins was ca. 0.15 kg smaller at the gestational age of 34 weeks, increasing to ca. 0.5 kg at 42 weeks of gestation. As for birth order, the mean birthweight of the first-born twin was heavier than that of the second-born. The standard deviation of birthweight was larger for second-born twins. The birthweight of twins from multiparous mothers was greater than those from primiparous mothers. The median birthweight according to gestational age was found to be the greatest in twins, lower in triplets and the lowest in quadruplets. In triplets, the 50(th )percentile was 0.08 kg heavier in boys than for girls. CONCLUSION: Our results can be used for assessment of birthweight of multiple births in Japan.